Statistics: dealing with categorical data. (28th November 2012) - Scott, M.; Flaherty, D.; Currall, J.
<x xml:space="preserve">Abstract</x> This, the fifth of our series of articles on statistics in veterinary medicine, moves onto modelling categorical data, in particular assessing associations between variables. Some of the questions we shall consider are widely discussed in many clinical research publications, and we will use the ideas of hypothesis tests and confidence intervals to answer those questions.